Ontology Visualization in BioPortal: Methodological Triangulation for Analyzing Accessibility, Communicability, and Usability - Cardoso, Daiane de Ascenção; Henriques, Felipe da Rocha; Belloze, Kele Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Visualizing biomedical ontologies is an ongoing and highly relevant challenge in dealing with the vast volume of daily data and the miscellaneous use cases of ontologies. BioPortal is the most wellknown tool for visualizing biomedical ontologies, bringing together hundreds of ontologies of varying sizes, depths, and complexities. This article aims to establish a methodological triangulation using SIM-SR based on Semiotic Engineering, the WCAG guidelines from the W3C consortium, and ergonomic principles to evaluate the experience of users who utilize screen readers and users who do not use this feature without conducting user experiments. The objective is to investigate and intersect the usability, communicability, and accessibility of BioPortal. Additionally, it seeks to understand how ontologies can be analyzed by as many people as possible, ensuring they are comprehensible and enhancing users’ cognitive understanding of the explored domain.